Data Speaks: District Clustering Map to Reveal Basic Education Problems in Samarinda City - Oroh, Chiko Zet; Dani, Andrea Tri Rian; Muawanah, Chusnul; Sitinjak, Jesselin Paskalis; Ibaad, Muhammad Irsadul; Mislan, Mislan; Kosasih, Raditya Arya (Darul Yasin Al Sys, 2024)
Education is an effort to create a learning environment and educational process that encourages the development of students' potential. One of the statistical methods that can be used in the field of education is cluster analysis. Average linkage is a hierarchical clustering algorithm that groups objects based on the average distance between objects in different clusters. In this study, sub-districts were grouped based on education indicators at the primary/elementary level in Samarinda City in 2023. The results of this research obtained 2 clusters that were the most optimal because they had the highest Silhouette coefficient value. Cluster 1 contains the subdistricts of Samarinda Ulu and Sungai Kunjang, while cluster 2 contains the subdistricts of North Samarinda, Palaran, Sungai Pinang, Sambutan, Loa Janan Ilir, Samarinda Ilir, Samarinda Seberang, and Samarinda Kota. Cluster 1 has an advantage over cluster 2 in several aspects of education. Cluster 1 shows a higher average in terms of the number of students, the number of classrooms, the number of institutions, the number of certified teachers, and the number of A-accredited schools at the primary/secondary level in Kota Samarinda in 2023.